Catálogo de los murciélagos de la región del delta del Río Colorado, México - Guevara-Carrizales, Aldo A.; Zamora-Gutiérrez, Verónica; Gonzáles-Gómez, Ricardo; Martínez-Gallardo, Roberto (THERYA, 2013)
The area of the Colorado River Delta is recognized as a priority terrestrial region that includes ecologically important areas such as Biosphere Reserve Upper Gulf of California and Colorado River Delta. In spite of its biological value, the current knowledge of the bat community is scarce. Therefore, this study aims to develop the first catalog of the bats of this region, in order to increase and update the knowledge of this group of mammals. We documented 34 records of voucher specimens from scientific collections, and complemented this list with field collections during the summer of 2006 and 2010, using of combined manner mist nets and bat detectors (Anabat II â„¢ and SD1â„¢ models). We collected 118 specimens and identified 1,525 records of echolocation calls. Nine species were registered for the region of Colorado River Delta, which belong to three families and eight genera. Antrozous pallidus is recorded for the first time in the study area. Our results confirm the importance of the combined use of mist nets and bat detectors for increasing the quality and quantity of information for the bat inventories. Key words: Baja California, bats, Chiroptera, Colorado River, conservation, Sonora.